The cyclin E regulator cullin 3 prevents mouse hepatic progenitor cells from becoming tumor-initiating cells - Kossatz-Böhlert, Uta; Breuhahn, Kai; Wolf, Benita; Hardtke-Wolenski, Matthias; Wilkens, Ludwig; Steinemann, Doris; Singer, Stephan; Brass, Felicitas; Kubicka, Stefan; Schlegelberger, Brigitte; Schirmacher, Peter; Manns, Michael P.; et al. (The journal of clinical investigation, 2010)
Cyclin E is often overexpressed in cancer tissue, leading to genetic instability and aneuploidy. Cullin 3 (Cul3) is a component of the BTB-Cul3-Rbx1 (BCR) ubiquitin ligase that is involved in the turnover of cyclin E. Here we show that liver-specific ablation of Cul3 in mice results in the persistence and massive expansion of hepatic progenitor cells.
Gesehen am 22.03.2023